Perception and attitude regarding underutilized plant species in Gowainghat upazila, Sylhet: Farmers’ Perception of Neglected and Underutilized Plant Species (NUPS) - Ghosh, Chayon Raj; Das, Subrata; Sharif, Md Omor; Talucder, Mohammad Samiul Ahsan (Journal of the Sylhet Agricultural University, 2026)
Global food systems are advancing towards vulnerable due to over reliance on a narrow range of staple crops (rice, wheat, maize), creating risks from climate change, environmental degradation, and malnutrition. Neglected and underutilized plant species (NUPS), are known as Future Smart Foods which are offering climate-resilient, nutrient-dense alternatives adapted to marginal environments, with potential dietary diversity, ability to combat hidden hunger, and support sustainable livelihoods. This study was conducted with the objectives of knowing the people perception and attitude towards the NUPS in Gowainghat Upazila of Sylhet District, Bangladesh. The research area is located in a humid sub-tropical region with heavy monsoon rainfall (~5,000 mm annually) and having diverse agroecology covering 200 randomly selected respondents from four unions (Fatehpur, Rustampur, Purba Jaflong, Alirgaon) with the above objectives during June 2022 to and April 2023. Data were collected by using semi-structured interviews, pre-tested questionnaires, field observations, and focus group discussions. The data were analyzed using descriptive statistics and Likert scales. Results revealed strong appreciation for NUPS, with fruits dominating usage (55.5%) followed by vegetables (16.5%) and medicinal applications (15%), and were primarily for self-consumption (55%) and contributing to nutrition, health, and income security. Women played the prominent role in labor-intensive production tasks (e.g., planting 57.5%, harvesting 65.5%), creating gender empowerment, while marketing remained male-dominated (71.5%). Respondents hold positive attitudes toward NUPS benefits including nutritional security and women's empowerment. But showed low awareness of environmental contributions (e.g., biodiversity enhancement), limited knowledge levels (47% nil), with a perceived decadal decline in availability/production (66.5%) attributed to marketing constraints (79 % respondents), uneven precipitation (72%), lack of training (69%), and inadequate knowledge (64%). These findings are aligned with global patterns of NUPS erosion due to policy negligence and climate stresses. The study underscores NUPS' viability as climate-smart resources in vulnerable rural Bangladesh, affirming their role in advancing SDGs 1 (No Poverty), 2 (Zero Hunger), 3 (Good Health and Well-being), 5 (Gender Equality), and 15 (Life on Land). Promoting awareness, gender-inclusive training, market linkages, and resilient cultivation could reverse declining, boost up food/nutrition security, and foster diversified, sustainable food systems in similar agroecological contexts. J. Sylhet Agril. Univ. 12(2): 117-126, 2025